A Fuzzy-Based Expert System for Prenatal Care Advice - Lukman OGUNDELE; Adekunle Ejidokun; Femi Ayo; Abass TAIWO (College of Education for Pure Sciences, 2024)
Prenatal care refers to medical attention that a woman receives to maintain her health and the health of her unborn child. The traditional methods of medical experts in prenatal care advice can sometimes be inadequate and less efficient due to a number of factors. One major issue is the lack of knowledge in the area of prenatal care for most medical experts, which hinders quality advice to pregnant women. In order to overcome some of these challenges, computer-based methods for any health issue have been proposed, which have shown to be more effective and are being utilized more frequently to raise the standard of medical care. This research work proposes the use of an expert system approach based on a forward-chain inference engine. Java programming language was used in the implementation of the proposed expert system. The expert system for prenatal care recommendations had a mean satisfaction level score of 3.87 out of a possible 5.0, according to the assessment results based on survey opinions. This suggests a 77.5% level of user satisfaction. The performance level of the expert system in providing quality advice to pregnant women indicates that it is faster, more sensitive, and more reliable than the traditional method of using medical experts to provide prenatal care advice.